What evidence is there for the existence of individual genes with antagonistic pleiotropic effects? - KARTAL ÖZER, NESRİN (ELSEVIER IRELAND LTD, 2005)
Classical evolutionary theory predicts the existence of genes with antagonistic effects on longevity and various components of early-life fitness. Quantitative genetic studies have provided convincing evidence that such genes exist. However, antagonistic pleiotropic effects have rarely been attributed to individual loci. We examine several classes of longevity-assurance genes: those involved in regulation of the gonad; the insulin-like growth factor pathway; free-radical scavenging; heat shock proteins and apoptosis. We find initial evidence that antagonistic pleiotropic effects are pervasive in each of these classes of genes and in various model systems-although most studies lack explicit studies of fitness components. This is particularly true of human studies. Very little is known about the early-life fitness effects of longevity loci. Given the possible medical importance of such effects we urge their future study. (C) 2004 Published by Elsevier Ireland Ltd.
Keywords: LIFE-SPAN; CAENORHABDITIS-ELEGANS; MOLECULAR SIGNALS; NATURAL-SELECTION; INDUCED APOPTOSIS; OXIDATIVE STRESS; CELL-DEATH; LONGEVITY; SENESCENCE; RECEPTOR